The Effect of Group Cohesivity, Working Satisfaction, And Team Effectivity Toward Senior High School Teachers Working Productivity - Hidayah, Nur; Widodo, Suparno Eko; Abdullah, Thamrin (International Journal for Educational and Vocational Studies, 2020)
This research aims to determine the effect of group cohesivity, working satisfaction, team effectivity toward senior high school teachers working productivity in South Tangerang City.  This research involved 240 senior high teachers taken from the selected targeted population; senior high teachers of South Tangerang City, using a quantitative approach with a path analysis method. The results of the variable analysis indicated that the direct effect of group cohesiveness on work productivity was 0.225, the direct effect of job satisfaction on working productivity was 0.247. Meanwhile, the direct effect of team effectivity on working productivity was 0.239. Thus, to improve teachers working productivity, teachers are required to enhance group cohesivity, working satisfaction, and team effectivity.